Three-dimensional fatigue crack propagation simulation using extended finite element methods for steel grades S355 and S690 considering mean stress effects. (15th January 2021) - Xin, Haohui; Correia, José A.F.O.; Veljkovic, Milan
Highlights: The Walker equation is employed to consider the mean stress effects. Stocastic analysis is conducted to obtain fatigue crack growth rate with 95%, 97.7%, and 99% guarantee. A user-defined fatigue crack propagation subroutine was developed using phantom nodes-based extended finite element method (PN-XFEM) and Virtual Crack Closure Technique (VCCT). Abstract: The assessment of fatigue crack propagation of steel structures is essential and important especially to improve the application of high strength steel in construction. The load ratio R, reflecting mean stress effects, will be changed with crack extension in the steel structures with complicated geometry. In this paper, the Walker equation is employed to fit the fatigue crack propagation rate of steel grades S355 and S690 based on experimental data in the literature to incorporate the mean stress effects. The material fatigue crack propagation parameters with 95%, 97.7%, and 99% guarantee of Walker equation were obtained by a stochastic analysis using the Monte Carlo method. The fatigue life was firstly predicted by the analytical method and was used as a baseline for numerical fatigue crack propagation simulation. A user-defined fatigue crack propagation subroutine based on the Walker equation was developed using phantom nodes-based extended finite element method (PN-XFEM) and Virtual Crack Closure Technique (VCCT) to consider the mean stress effects. The proposed three-dimensional fatigue crack propagation simulation subroutine is successfully validated of both steel grades, S355 and S690.